Konseling Restrukturisasi Kognitif Bagi Peningkatan Subjective Well-Being Santri - Alfiyani, Devi; Sugiyadi, Sugiyadi; Kuniati, Astiwi (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2025)
Abstract: This study aims to determine group counselling services with Cognitive Restructuring Techniques for improving subjective well-being in female students of MBS Magelang City.This type of research is a Pre-Experimental Design research with One Group Pretest Posttest Design type. The research subjects were selected using simple random sampling technique. The sample in this study used 7 students as an experimental group. The data collection method was carried out using a subjective well-being identification questionnaire that had been tested for validity and reliability with the help of SPSS 26 for windows.The results showed that group counselling cognitive restructuring techniques effectively improve the subjective well-being of female students of MBS Magelang City. Proven by the results of pretest and posttest, the highest change score after treatment is 17 points or equivalent to 24.28%. Comparison of pretest and posttest scores above is corroborated by changes in santri behaviour, namely, individual changes that appear before being given counseling services and after being given cognitive restructuring group counseling. Abstrak: Penelitian ini bertujuan untuk mengetahui layanan konseling kelompok dengan Teknik Restrukturisasi Kognitif bagi peningkatan subjective well-being pada santri putri MBS Kota Magelang. Jenis penelitian ini merupakan penelitian Pre-Experimental Design dengan tipe One Group Pretest Posttest Design. Subjek penelitian dipilih menggunakan teknik simple random sampling. Sampel pada penelitian ini menggunakan 7 santri sebagai kelompok eksperimen. Metode pengumpulan data dilakukan menggunakan angket identifikasi subjective well-being yang sudah diuji validitas dan reabilitas dengan bantuan SPSS 26. For windows.Hasil penelitian menunjukkan bahwa konseling kelompok teknik restrukturisasi kognitif efektif meningkatkan subjective well-being santri putri MBS Kota Magelang. Dibuktikan hasil pretest dan posttest skor perubahan tertinggi setelah diberikan treatment yaitu sebesar 17 point atau setara dengan 24,28%. Perbandingan skor pretest dan posttest diatas dikuatkan dengan perubahan perilaku santri yaitu, perubahan individu yang tampak sebelum diberikan layanan konseling dan sesudah diberikan konseling kelompok restrukturisasi kognitif.